Binding, Release and Functionalization of Intact Pnictogen Tetrahedra Coordinated to Dicopper Complexes. Issue 45 (23rd June 2022) - Piesch, Martin; Nicolay, Amélie; Haimerl, Maria; Seidl, Michael; Balázs, Gábor; Don Tilley, T.; Scheer, Manfred
Abstract: The bridging MeCN ligand in the dicopper(I) complexes [(DPFN)Cu2 (μ, η 1 : η 1 ‐MeCN)][X]2 (X=weakly coordinating anion, NTf2 (1 a ), FAl[OC6 F10 (C6 F5 )]3 (1 b ), Al[OC(CF3 )3 ]4 (1 c )) was replaced by white phosphorus (P4 ) or yellow arsenic (As4 ) to yield [(DPFN)Cu2 (μ, η 2 : η 2 ‐E4 )][X]2 (E=P (2 a –c ), As (3 a –c )). The molecular structures in the solid state reveal novel coordination modes for E4 tetrahedra bonded to coinage metal ions. Experimental data and quantum chemical computations provide information concerning perturbations to the bonding in coordinated E4 tetrahedra. Reactions with N‐heterocyclic carbenes (NHCs) led to replacement of the E4 tetrahedra with release of P4 or As4 and formation of [(DPFN)Cu2 (μ, η 1 : η 1 ‐ Me NHC)][X]2 (4 a, b ) or to an opening of one E−E bond leading to an unusual E4 butterfly structural motif in [(DPFN)Cu2 (μ, η 1 : η 1 ‐E4 Dipp NHC)][X]2 (E=P (5 a, b ), E=As (6 )). With a cyclic alkyl amino carbene ( Et CAAC), cleavage of two As−As bonds was observed to give two isomers of [(DPFN)Cu2 (μ, η 2 : η 2 ‐As4 Et CAAC)][X]2 (7 a, b ) with an unusual As4 ‐triangle+1 unit. Abstract : The bridging MeCN ligand in the dicopper(I) complex [(DPFN)Cu2 (μ, η 1 : η 1 ‐MeCN)][X]2 (X=WCA) can easily be replaced by white phosphorus (P4 ) or yellow arsenic (As4 ) to yield [(DPFN)Cu2 (μ, η 2 : η 2 ‐E4 )][X]2 (E=P, As). The coordinated intact E4 tetrahedra can be further selectively functionalized with N‐heterocyclic carbenes (NHCs) and cyclic alkyl amino carbenes (CAACs) under cleavage of E−E bonds, while using a small and strong NHC leads to the release of the pnictogen tetrahedra as P4 and grey arsenic, respectively.